HEALTH SECTOR CORRUPTION AS THE ARCHENEMY OF UNIVERSAL HEALTH CARE IN INDONESIA - Ratna Juwita (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThis article argues that health sector corruption is a direct threat towards universal health care in Indonesia. Three Indonesian legal cases of health sector corruption are selected to exemplify the reality of health sector corruption and it’s detrimental effect to the realization of the right to health. This article emphasizes that corruption causes misallocation and embezzlement of the fund that hampers the State party to optimally provide universal health care for the people. This article suggests that in order to establish quality and sustainable universal health care as an instrument for the realization of the right to health, the State party has to prioritize on the elimination of health sector corruption.Keywords: corruption, Indonesia, right to health, health care.IntisariArtikel ini membahas perihal korupsi di sektor kesehatan yang merupakan ancaman bagi perlindungan kesehatan universal di Indonesia. Tiga kasus hukum mengenai korupsi di sektor kesehatan dipilih untuk memberikan gambaran mengenai korupsi di sektor kesehatan dan dampak negatifnya terhadap realisasi hak atas kesehatan. Artikel ini menekankan bahwa korupsi menyebabkan misalokasi dan penggelapan dana yang menghambat Negara pihak dalam penyediaan pelayanan kesehatan yang optimal bagi semua orang. Artikel ini menyarankan bahwa dalam rangka untuk menyelenggarakan perlindungan kesehatan universal yang berkualitas dan berkelanjutan sebagai instrumen untuk merealisasikan hak atas kesehatan, Negara pihak harus memprioritaskan pemberantasan korupsi di sektor kesehatan.Kata kunci: korupsi, Indonesia, hak atas kesehatan, perlindungan kesehatan.